Fortification of yogurts with different antioxidant preservatives: a comparative study between natural and synthetic additives - Caleja, Cristina (2016)
Consumers demand more and more so-called "natural" products and, therefore, the aim of this work was to compare the effects of natural versus synthetic antioxidant preservatives in yogurts. Matricaria recutita L. (chamomile) and Foeniculum vulgare Mill. (fennel) decoctions were tested as natural additives, while potassium sorbate (E202) was used as a synthetic additive. The fortification of yogurts with natural and synthetic antioxidants did not cause significant changes in the yoghurt pH and nutritional value, in comparison with control samples (yogurt without any additive). However, the fortified yogurts showed higher antioxidant activity, mainly the yogurts with natural additives (and among these, the ones with chamomile decoction). Overall, it can be concluded that plant decoctions can be used to develop novel yogurts, by replacing synthetic preservatives and improving the antioxidant properties of the final product, without changing the nutritional profile.